Metacognitive Skills As A Guidance Curriculum In The Age Of AI - Suryahadikusumah, Ahmad Rofi; Monalisa, Monalisa; Syaputra, Yogi Damai; Ramanda, Peni; Nurmalasari, Yuli; Fahriza, Irfan; Nadya, Aisha (Psikopedagogia, 2024)
The existence of Artificial Intelligence (AI) in educational practice should increase mobility and learning outcomes and improve student learning skills. On the other hand, students see AI as a system that helps them complete practical learning tasks. This condition creates a conflict and a dilemma in using AI in learning. Studies on AI in education recommend metacognitive as an essential ability for students to utilize AI well. The research aims to find the formulation of the metacognitive competencies students need in using AI as content in curriculum guidance. The research method uses the Systematic Literature Review with the PRISMA model. The literature review results show that metacognitive studies in adolescent education and development refer to longitudinal studies conducted by Roger Azevedo. Guidance curriculum in improving metacognitive skills related to the use of AI are 1) self-regulation, 2) critical thinking, and 3) decision-making process. Guidance activities that can be carried out in  developing metacognitive must be inquiry – oriented such as pair activity (brainstorming), self-assessment, experiential activity, and information selection.